Band structure and microstructure modulations enable high quality factor to elevate thermoelectric performance in Ge0.9Sb0.1Te-x%FeTe2. (September 2021) - Jin, Yang; Hong, Tao; Wang, Dongyang; Xiao, Yu; He, Wenke; Gao, Xiang; Qiu, Yuting; Zhao, Li-Dong
Abstract: GeTe is an excellent mid-temperature thermoelectric material with various freedom degrees to tune the thermoelectric performance, which has drawn intensive attentions. Herein, superior thermoelectric performance of GeTe-based materials is achieved through significantly elevating quality factor B with FeTe2 introduction. First-principles calculations show that introducing FeTe2 into GeTe can increase the density of states due to the contribution of the 3d orbital of Fe, leading to an enhancement of effective mass from ∼2.21 m 0 in Fe-free sample to ∼3.01 m 0 in Ge0.9 Sb0.1 Te–2%FeTe2, which could maintain high electrical transport properties. Meanwhile, the lattice thermal conductivity is drastically suppressed by Van der Waals gaps, Fe-rich nanoprecipitates and strain field fluctuations with minimal disruption on carrier transport, leading to a minimum lattice thermal conductivity of ∼0.54 Wm -1 K −1 . Ultimately, a superior ZT ∼2.1 at 723 K and a ZT ave of ∼1.25 at 300–773 K are attained in Ge0.9 Sb0.1 Te–1%FeTe2 . Graphical abstract: Image 1 Highlights: Superior thermoelectric property of GeTe-based materials is achieved via elevating quality factor with FeTe2 introduction. Introducing FeTe2 increases the effective mass from ∼2.21m0 –∼3.01 m0 through enlarging density of states. A minimum κ lat ∼0.54 Wm -1 K −1 is achieved via incorporating Fe-rich nanoprecipitates and Van der Waals gaps into the matrix. A superior ZT ∼2.1 at 723 K and a ZT ave of ∼1.25 at 300–773 K are acquired in Ge0.9 Sb0.1 Te–1%FeTe2 .